Breast cancer–related deaths according to grade in ductal carcinoma in situ: A Dutch population–based study on patients diagnosed between 1999 and 2012. (September 2018) - van Maaren, M.C.; Lagendijk, M.; Tilanus-Linthorst, M.M.A.; de Munck, L.; Pijnappel, R.M.; Schmidt, M.K.; Wesseling, J.; Koppert, L.B.; Siesling, S.
Abstract: Background: The incidence of ductal carcinoma in situ (DCIS) has drastically increased over the past decades. Because DCIS is resected after diagnosis similar to invasive breast cancer, the natural cause and behaviour of DCIS is not well known. We aimed to determine breast cancer–specific survival (BCSS) and overall survival (OS) according to grade in DCIS patients after surgical treatment in the Netherlands. Patients and methods: All DCIS patients diagnosed between 1999 and 2012 were selected from the Netherlands Cancer Registry. The cause of death was obtained from 'Statistics Netherlands'. BCSS and OS were estimated using multivariable Cox regression in the entire cohort and stratified for grades. Results: In total, 12, 256 patients were included, of whom 1509 (12.3%) presented with grade I, 3675 (30.0%) with grade II, 6064 (49.5%) with grade III and 1008 (8.2%) with an unknown grade. During a median follow-up of 7.8 years, 1138 (9.3%) deaths were observed, and 179 (1.5%) were breast cancer–related. Of these, 10 patients had grade I; 46 grade II; 95 grade III and 28 an unknown grade. After adjustment for confounding, grade II and III were related to worse BCSS than grade I with hazard ratios of 1.92 (95% confidence interval [CI]: 0.97–3.81) and 2.14 (95% CI: 1.11–4.12), respectively. No association between grades and OS was observed. Conclusion: BCSS and OS in DCIS patients were excellent. Because superior rates were observed for low-grade DCIS, it seems justified to investigate whether active surveillance may be a balanced alternative for conventional surgical treatment. Highlights: Ductal carcinoma in situ (DCIS) patients are currently treated similarly to invasive breast cancer patients. After a median follow-up of 7.8 years, 1.5% of all patients died of breast cancer. In grade I patients, only 0.7% died due to breast cancer. Active surveillance may be a balanced alternative for conventional surgery in low-grade DCIS.